NUTRITIONAL VALUE AND SUITABILITY OF CARROT WHOLE TOP AS GREEN FODDER - R. Venkataramanan; S. Gunasekaran; C. Sreekumar; R. Anilkumar; M. Iyue (Indian Journal of Veterinary and Animal Sciences Research, 2024)
The carrot tops had high crude protein (144 g/kg), calcium (24.3 g/kg) and phosphorus (7.7 g/kg), comparable to sun hemp (Crotalaria junctea), fodder berseem and oil cakes, respectively. Milk from animals fed with carrot tops were free from residues of organochlorine, carbamate and organophosphorus pesticides. Carrot tops are perishable in nature and hence were preserved as feed blocks to extend shelf life. The nutritional value and keeping quality of the blocks were also studied. The studies revealed that carrot whole tops can be a promising alternate source of green fodder, especially in hilly regions where there is a shortage of green fodder during winter.